Qualitative study of healthcare providers’ current practice patterns and barriers to successful rehydration for pediatric diarrheal illnesses in Kenya - House,Darlene R.; Cheptinga,Philip; Rusyniak,Daniel E.; Vreeman,Rachel C. (PeerJ, 2017)
Background For children worldwide, diarrhea is the second leading cause of death. These deaths are preventable by fluid resuscitation. Nasogastric tubes (NGs) have been shown to be equivalent to intravenous fluids for rehydration and recommended by the World Health Organization (WHO) for use in severe dehydration. Despite this, NGs are rarely used for rehydration in Kenya. Our objective was to evaluate clinicians’ adherence to rehydration guidelines and to identify barriers to the use of NGs for resuscitating dehydrated children. Methods A case-based structured survey was administered to pediatric care providers in western Kenya to determine their choices for alternative rehydration therapies when oral rehydration and intravenous fluids fail. Providers then participated in a qualitative, semi-structured interview to identify barriers to using nasogastric tubes for rehydration. Analysis included manual, progressive coding of interview transcripts to identify emerging central themes. Results Of 44 participants, only four (9%) followed WHO guidelines that recommend quickly switching to NG for rehydration in their case responses. Participants identified that placing intravenous lines in dehydrated children is a challenge. However, when discussing NG use, many believed NGs are not effective for rehydration. Other participants’ concerns surrounded knowledge and training regarding guidelines as well as not having NGs available. Discussion Healthcare providers in western Kenya do not report using NGs for rehydration in accordance with WHO guidelines for diarrheal illness with severe dehydration. Barriers to the use of NG tubes were lack of knowledge and availability. Education and implementation of guidelines using NG tubes for rehydration may improve outcomes of children suffering from diarrheal illness with severe dehydration.
Keywords: Resuscitation/methods; Pediatrics; Child; Diarrhea; Fluid therapy